Use of a proximity extension assay proteomics chip to discover new biomarkers associated with albuminuria. (March 2017) - Carlsson, Axel C; Sundström, Johan; Carrero, Juan Jesus; Gustafsson, Stefan; Stenemo, Markus; Larsson, Anders; Lind, Lars; Ärnlöv, Johan
Background: The underlying mechanisms for the development of albuminuria and the increased cardiovascular risk in patients with elevated albuminuria levels are incompletely understood. We therefore investigated the associations between 80 cardiovascular proteins and the urinary albumin to creatinine ratio (ACR). Methods: We used a discovery/replication approach in two independent community-based cohorts of elderly patients: the Uppsala Longitudinal Study of Adult Men ( n  = 662; mean age 78 years) and the Prospective Investigation of the Vasculature in Uppsala Seniors ( n  = 757; mean age 75 years; 51% women). A proteomic chip with a panel of 80 plasma proteins associated with different aspects of cardiovascular disease was analysed. In the discovery cohort, we used a false discovery rate of 5% to take into account the multiple statistical testing. Nominal p values were used in the replication. Results: Higher levels of T-cell immunoglobulin mucin-1, placenta growth factor, growth/differentiation factor-15, urokinase plasminogen activator surface receptor and kallikrein-11 were robustly associated with a higher ACR in both cohorts in multivariable linear regression models adjusted for sex, established cardiovascular risk factors, antihypertensive treatment, prevalent cardiovascular disease and glomerular filtration rate ( p  < 0.02 for all). All associations were also significant in separate analyses of patients without diabetes. Conclusions: We discovered and replicated associations between ACR and five cardiovascular proteins involved in tubular injury, atherosclerosis, endothelial function, heart failure, inflammation, glomerulosclerosis and podocyte injury. Our findings put forward multiplex proteomics as a promising approach to explore novel aspects of the complex detrimental interplay between kidney function and the cardiovascular system.